Lanskap Linguistik Museum di Madura: Studi Kasus Museum Mandhilaras Pamekasan Madura - Mohammad Syaiful Rohman; M. Masqotul Imam Romadlani (Journal of Social, Culture, and Language, 2023)
Linguistic landscape is a practice of using language in public spaces. This research describes the use of language found in the labeling of historical heritage objects, especially those stored at the Madura Mandhilaras Pamekasan Museum (MMP), using a linear landscape approach. This research uses qualitative and quantitative methods which will explain the use of language along with the percentage of language variants at the Mandhilaras Pamekasan Museum. The objects taken from this museum are 200 photographs that have been captured. of these photos, the number of labels that use monolingualism is 23, then those that use bilingualism are 35, while those that use it are 0. These photos will later be discussed from two discussion elements, namely Monolingualism, Bilingualism and Multilingualism to be used as an analysis. The research results show that the language used is dominantly monolingual. In essence, language use that uses one language is considered monolingual, while those that use two languages include bilingual, and finally if you use 3 languages, it is considered multilingual. The results of the research show that the language used is predominantly monolingual.Keywords: Language; museum; pictures; reasearch